تأثير استخدام قاذف الكرات لتعلم مهارتي الضربتين الأرضيتين الأمامية والخلفية باسلوب تعلم الإتقاني بالتنس الأرضي للاعبين للمبتدئين - حسن, ازاد علي (Sulaimani Journal for Humanities, 2018)
Summary Part I contains the section on the front and the importance of research and touched the researcher to scientific progress in the world who has made physical education depends linked to science other and that scientific methods and methods are the greatest guarantee the realization of the different needs in various sports fields relying on research and through teaching methods and methods used by trainers. The research problem has felt the researcher need to work in a way of learning Alatghani very convenient because it is to take into account individual differences among players and novice using (thrower balls) which gives practice and repetition right and abundance for all learners and eliminates individual differences and reach all learners to a good level of skill ability skills of basic tennis and private (my skills Aldharptin front and rear earth stations). Seat1- goal - to identify the impact of learning style Alatghani using thrower balls in learning my skills (Aldharptin front and rear earth stations) in tennis for beginners. 1. Find presumably there are significant differences between pretest and posttest for your endurance tests of the effectiveness of 100m hurdles 2. differences there are significant differences between the post tests of the research group to test your endurance to the effectiveness of 100m hurdles Research Hypothesis: - The style of learning Alatghani using balls thrower has a positive effect on learning my skills (Aldharptin front and rear earth stations) in tennis for beginners. areas of research: human sphere: a sample of the fourth stage novices. temporal sphere: from 12.01.2016 till 03.03.2017. spatial field: Playgrounds Faculty of Physical Education in Khanaqin. The second section Vttrq to the concept of learning Alatghani: its learning Alatghani means the group educated to reach the degree of perfection in learning and performance before moving on to learn other skills more complex and difficult, and that this method takes into account individual differences among members of the same group and the team one, it may be modules enough to teach some individuals and not enough for others, and this means that others need more duplicates and more attention for the purpose of members of all the group access to the degree of perfection that the basic skills learned in a satisfactory manner and the average does not allow the transfer of learners to the top of the stage, a stage tactically because the foundation is weak, "as The tactical phase requires that the learner leads basic skills automatically (automatic) and without the attention and effectively. The third chapter included this section Display search methodology used experimental method and a sample totaling 40 students as well as the tools used in the search, as well as the appropriate statistical methods for the purpose of processing results and a way that serves the research. Part IV included this section view and analyze the findings of a researcher and then discussed scientific Ballot some of which shows the results of tests tribal and dimensionality of the control and experimental groups for my skills Aldharptin front and rear earth stations. The Title V included the conclusions and recommendations reached by the researcher Conclusions through the presentation of the results of the tests and analyzed and discussed, the researcher was able to reach the following conclusions: 1. The emergence of a clear improvement in learning two sets of research (experimental and control group) for Mhartin core (foreground strike back and strike the earth). 2. outweigh the experimental group that used the style of learning Alatghani in the amount of learning the control group used traditional learning style (Prince) in the basic skills are (foreground strike and strike ground the background). The most important Altusiat1- emphasis on the use of learning style Alatghani using thrower balls in learning the basic skills in tennis ground, especially my skills (Aldharptin front and rear earth stations) to the fact that the balls thrower means learning positive for beginners.